Is India Economically Healthy? - Shabbir, Danish (International Journal of Psychosocial Rehabilitation, 2020)
Economically healthy has many perspectives which includes financial health of a country, the monetary system, the fiscal policies, the banking structure functioning, the taxation system, the new roll-outs such as GST, the stock market functioning, the interest rates, inflation rates, forex, GDP figures, household conception, savings, young population, debt structure, foreign reserves etc. India is a developing country and among the plethora of examples, this paper shall be highlighting few topics such as GDP (Gross Domestic Product) which is the main indicator of a country’s health along with its partnering factors. In this paper India will be taken as a sample and the method used shall be in graphical and tabular in percentage format. The long-term perspective is very positive about Indian economy on the whole making it is a strong and developing country which is indeed economically healthy no matter in short term perspective the challenges and turbulences keep on hindering its pace of growth. According to a report by PWC (price water house copper) India can take over US by 2050 or so in terms of purchasing power where India is currently standing at 3rd position.